COMPUTERIZATION OF BUDGETARY PROCESSES IN THE STATES. - Kelly, Frank; Stenberg, Carl W. (Public Administration Review)
This article discusses the ways in which computerization can and has been applied to state budgetary processes in the U.S. as of July 1978. With rapidly declining computer prices and increasing numbers of computer technicians, it is not surprising that the budgetary process in government is becoming increasingly computerized. The preparation of a budget is a laborious process involving several decision levels and including the drafting and refinement of textual justification, the repeated calculation of financial tables, and a constant effort to maintain consistency among the tables themselves and between the tables and the text. The budget process in most, if not all jurisdictions, faces substantial time constraints, and the number of options that can be considered is significantly limited by the time available to do the calculations necessary to cost out each option. The computer, which performs calculations at a rate many times faster than a human offers a means of freeing personnel from most routine calculating tasks and thus permits a greater role for analysis in the budgetary process.